A polypyrrole-cotton pad sorbent as micro-solid phase extractor enclosed in tea bag envelope for determination of synthetic antioxidants in non-alcoholic beverage products. Issue 4 (3rd April 2023) - Maneeratanachot, Suwatchanee; Kanatharana, Proespichaya; Thammakhet-Buranachai, Chongdee; Wattanasin, Panwadee
Abstract: A polypyrrole (PPy)-cotton pad sorbent enclosed in tea bag envelope was developed and used in micro-solid phase extraction (µ-SPE) for the determination of butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT). After extraction, the extract was qualified and quantified by a gas chromatograph equipped with a flame ionization detector (GC-FID). Parameters influencing this developed method and the efficiency of µ-SPE were studied and optimized. Under the optimal conditions, the developed method provided good linearity in a concentration range of 0.100–100 µg L −1 for BHA and 0.050–50 µg L −1 for BHT, respectively. The limits of detection were 39.27 ± 0.52 ng L −1 for BHA and 16.96 ± 0.17 ng L −1 for BHT. Satisfactory relative recoveries of BHA and BHT were achieved in the range from 86.8 ± 1.9 to 117.1 ± 2.3% with acceptable relative standard deviation (RSD) below 8.1%. Good reproducibility was obtained with RSDs < 3.1%, for n  = 6. The developed adsorbent is easy to operate, low cost, eco-friendly, reusable, with high extraction efficiency, and was successfully applied in the simultaneous synthetic antioxidant determination of non-alcoholic beverage samples.